1985
DOI: 10.1007/bf00392207
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A is synthesized as a glycoprotein precursor

Abstract: Concanavalin A (Con A) is a tetrameric lectin which is synthesized in the cotyledons of developing jack-bean (Canavalia ensiformis (L.) D.C.) seeds and accumulates in the protein bodies of storage-parenchyma cells. The polypeptides of Con A have a molecular weight of 27000 and a relative molecular mass (Mr) of 30000 when analyzed by gel electrophoresis on denaturing polyacrylamide gels. In-vitro translation of RNA isolated from immature jack-bean cotyledons shows that Con A is synthesized as a polypeptide with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 34 publications
0
29
1
Order By: Relevance
“…The presence of a GlcNAc # Man ( glycan on the precursor would give a theoretical molecular mass change of 1541 Da on deglycosylation, which lies within the predicted accuracy of the measured values. This value of 1550 Da, corresponding to an oligosaccharide composition of GlcNAc # Man ( , contrasts with a previous report that the Nglycan on the Con A precursor had a composition of GlcNAc # Man * [7]. This discrepancy suggests that trimming by α-mannosidase of outer mannose residues has taken place, either during seed development, in precursor purification or in storage.…”
Section: Figure 7 Dependence On Ph Of Jackbean N-glycanase Activitycontrasting
confidence: 66%
See 2 more Smart Citations
“…The presence of a GlcNAc # Man ( glycan on the precursor would give a theoretical molecular mass change of 1541 Da on deglycosylation, which lies within the predicted accuracy of the measured values. This value of 1550 Da, corresponding to an oligosaccharide composition of GlcNAc # Man ( , contrasts with a previous report that the Nglycan on the Con A precursor had a composition of GlcNAc # Man * [7]. This discrepancy suggests that trimming by α-mannosidase of outer mannose residues has taken place, either during seed development, in precursor purification or in storage.…”
Section: Figure 7 Dependence On Ph Of Jackbean N-glycanase Activitycontrasting
confidence: 66%
“…The jackbean lectin, Con A, is synthesized as an inactive Nlinked glycoprotein, which undergoes a number of processing events involving deglycosylation, proteolysis and post-translational ligation of peptides to yield the mature protein [3][4][5][6][7][8][9][10][11][12]. Previously it has been shown that the essential step in converting the inactive precursor into an active lectin is deglycosylation [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At seed maturity the lectin is located in protein bodies of the storage parenchyma cells of the cotyledons, where it constitutes 20% of the total protein (Agrawal and Goldstein, 1976;Bowles, 1990b). Accumulation of Con A in the seed starts during the midstages of development when the newly synthesized protein is transported from the lumen of the rough endoplasmic reticulum (RER) through the Golgi apparatus to the vacuolar compartment (Herman and Shannon, 1984;Herman et al, 1985;Maycox et al, 1988). Protein loading into the vacuole is accompanied by progressive fragmentation of the compartment to give rise to the protein bodies (Bowles 1990a).…”
Section: Introductionmentioning
confidence: 99%
“…Concanavalin A precursor (spot 46), a precursor of nonenzymatic carbohydrate binding protein (lectin) present in the endoplasmic reticulum (Herman et al 1985) is a highmannose oligosaccharide which is processed to form mature con A which is non-glycosylated (Sheldon and Bowles 1992). Con A precursor in elute may be from the column itself as mature non-glycosylated con A is derived from its glycosylated precursor which upon modification forms the lectin (Chrispeels et al 1986).…”
Section: Protein Involved In Abiotic and Biotic Stress Tolerancementioning
confidence: 99%